A comparative, retrospective analysis of HIV testing among gay, bisexual and other men who have sex with men in Melbourne, Australia. (29th May 2019) - Ryan, Kathleen E.; Wilkinson, Anna L.; Chow, Eric; Read, Tim; Chen, Marcus; Locke, Peter; Leitinger, David; Bradshaw, Catriona; Pedrana, Alisa; Hellard, Margaret; Fairley, Christopher K.; Stoové, Mark
Abstract: Objective : PRONTO!, a peer‐led rapid HIV‐testing service in Melbourne, Australia, opened to improve HIV testing among gay and bisexual men (GBM). We compared client characteristics and return testing among GBM testing at PRONTO! with GBM testing at Melbourne Sexual Health Centre (MSHC). Methods : All GBM attending PRONTO! and MSHC for HIV testing between August 2013 and April 2016 were included. We describe the number of tests, percentage of clients who returned during follow‐up, the mean number of tests and median time between tests at the two services. Results : At PRONTO!, 33% of 3, 102 GBM and at MSHC 50% of 9, 836 GBM returned for a further HIV test at least once. The mean number of tests per client was 1.7 and 2.5 at PRONTO! and MSHC ( p <0.01), respectively. A majority of clients at both services reported behaviours that would recommend up to quarterly testing, however, the median time between tests was 20.0 and 17.0 weeks at PRONTO! and MSHC ( p <0.01), respectively. Conclusions : A greater proportion of clients returned and returned frequently at MSHC compared to PRONTO!, however, at both services HIV testing frequency was suboptimal. Implications for public health : Novel HIV testing services should provide convenient and comprehensive sexual health services.